Short implants and tooth-implant connections - Michel Abbou (Journal of Dental Problems and Solutions - Peertechz Publications, 2023)
Both short implants (<8mm) and tooth-implant connections are, to say the least, controversial therapeutic means. However, if we take a serious look at the data in the scientific literature, we can observe favorable clinical results in both areas, enabling these therapeutic options to be accepted as Evidence-Based Dentistry.